Micro-Injection Moulding of Polymer Microfluidic Devices - Attia, Usama M.; Marson, Silvia; Alcock, Jeffrey R. (Springer Science Business Media, 2009)
Microfluidic devices have several applications in different fields, such as chemistry, medicine and biotechnology. Many research activities are currently investigating the manufacturing of integrated microfluidic devices on a mass- production scale with relatively low costs. This is especially important for applications where disposable devices are used for medical analysis. Micromoulding of thermoplastic polymers is a developing process with great potential for producing low-cost microfluidic devices. Among different micromoulding techniques, micro-injection moulding is one of the most promising processes suitable for manufacturing polymeric disposable microfluidic devices. This review paper aims at presenting the main significant developments that have been achieved in different aspects of micro-injection moulding of microfluidic devices. Aspects covered include device design, machine capabilities, mould manufacturing, material selection and process parameters. Problems, challenges and potential areas for research are highlighted.
Keywords: Micro-injection moulding; Microfluidics; Polymers; Polymer processing